Prevalence and determinants of resistance mutations in HIV‐1‐infected patients exposed to integrase inhibitors in a large Italian cohort. Issue 2 (21st November 2018) - Modica, S; Rossetti, B; Lombardi, F; Lagi, F; Maffeo, M; D'Autilia, R; Pecorari, M; Vicenti, I; Bruzzone, B; Magnani, G; Paolucci, S; Francisci, D; et al.
Abstract : Objectives: The aim of the study was to analyse the prevalence of integrase resistance mutations in integrase strand transfer inhibitor (INSTI)‐experienced HIV‐1‐infected patients and its predictors. Methods: We selected HIV‐1 integrase sequences from the Antiviral Response Cohort Analysis (ARCA) database, derived from INSTI‐experienced patients between 2008 and 2017. Differences in the prevalence of resistance to raltegravir (RAL), elvitegravir (EVG) and dolutegravir (DTG) were assessed by χ 2 test and predictors of resistance were analysed by logistic regression. Results: We included 462 genotypes from INSTI‐exposed individuals: 356 'INSTI‐failing' patients and 106 'previously INSTI‐exposed' patients (obtained a median of 42 weeks after INSTI discontinuation [interquartile range (IQR) 17–110 weeks]). Overall, at least low‐level resistance (LLR) to any INSTI (Stanford 8.5 algorithm) was detected in 198 (42.9%) cases. The most frequent INSTI resistance mutation was N155H, followed by Q148H/K/R, G140A/C/S, E138A/K/T and Y143C/H/R. Y143R and E138A were more prevalent in viral subtype B versus non‐B [5.2 versus 1.5%, respectively ( P = 0.04), and 3.1 versus 0%, respectively ( P = 0.02)]. Overall, the Q148H/K/R plus G140A/C/S and/or E138A/K/T pattern, defining an intermediate level of resistance to DTG, was detected in 70 (15%) cases. Independent predictors of at least LLR to any INSTI were current use versus past use of INSTIs, a lower genotypic sensitivity score (GSS) for contemporary antiretroviral drugs used, and having an integrase sequence obtained in calendar year 2016 as compared to 2008–2009. Conclusions: The results support integrase resistance testing in INSTI‐experienced patients. Emergence of INSTI resistance is facilitated by the reduced genetic barrier of the regimen as a consequence of resistance to companion drugs. However, INSTI resistance may become undetectable by standard population sequencing upon INSTI discontinuation.